Systematic review of surgery and outcomes in patients with primary aldosteronism. Issue 4 (20th January 2015) - Muth, A.; Ragnarsson, O.; Johannsson, G.; Wängberg, B.
Abstract Background Primary aldosteronism (PA) is the most common cause of secondary hypertension. The main aims of this paper were to review outcome after surgical versus medical treatment of PA and partial versus total adrenalectomy in patients with PA. Methods Relevant medical literature from PubMed, the Cochrane Library and Embase OvidSP from 1985 to June 2014 was reviewed. Results Of 2036 records, 43 articles were included in the final analysis. Twenty‐one addressed surgical versus medical treatment of PA, four considered partial versus total adrenalectomy for unilateral PA, and 18 series reported on surgical outcomes. Owing to the heterogeneity of protocols and reported outcomes, only a qualitative analysis was performed. In six studies, surgical and medical treatment had comparable outcomes concerning blood pressure, whereas six showed better outcome after surgery. No differences were seen in cardiovascular complications, but surgery was associated with the use of fewer antihypertensive medications after surgery, improved quality of life, and (possibly) lower all‐cause mortality compared with medical treatment. Randomized studies indicate a role for partial adrenalectomy in PA, but the high rate of multiple adenomas or adenoma combined with hyperplasia in localized disease is disconcerting. Surgery for unilateral dominant PA normalized BP in a mean of 42 (range 20–72) per cent and the biochemical profile in 96–100 per cent of patients. The mean complication rate in 1056 patients was 4·7 per cent. Conclusion Recommendations for treatment of PA are hampered by the lack of randomized trials, but support surgical resection of unilateral disease. Partial adrenalectomy may be an option in selected patients.